2012
DOI: 10.1051/matecconf/20120201009
|View full text |Cite
|
Sign up to set email alerts
|

Etude du comportement mécanique de liants binaires et ternaires à base de ciment Portland, de laitier de haut fourneau et de filler calcaire

Abstract: Abstract. The main objective of this study is to detect the influence of the addition of limestone fillers in moderate percentages (0%, 10% and 20%) on the performance of binder formulations containing different dosages of blast furnace slag (ranging from 20% to 80%). The analysis parameters are mercury intrusion porosity and mechanical properties. The tests were performed on 12 blended pastes made with a water/cement ratio equal to 0.32. The mechanical properties of different pastes were investigated at sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The use of a ternary binder (cement, silica fume, and granulated slag) is one of the recent areas of research, which aims to improve HPC durability and mechanical behavior, and minimize the negative environmental impacts. Cementitious materials made of ternary binders can in fact exhibit superior performance to those based on binary binders in terms of heat release, mechanical resistance at early ages, and durability [16,17]. Several research studies have reported that the incorporation of silica fume combined with other mineral additions (pozzolan, blast furnace slag, or fly ash) in the cement matrix improves the mechanical properties and the durability of HPC [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a ternary binder (cement, silica fume, and granulated slag) is one of the recent areas of research, which aims to improve HPC durability and mechanical behavior, and minimize the negative environmental impacts. Cementitious materials made of ternary binders can in fact exhibit superior performance to those based on binary binders in terms of heat release, mechanical resistance at early ages, and durability [16,17]. Several research studies have reported that the incorporation of silica fume combined with other mineral additions (pozzolan, blast furnace slag, or fly ash) in the cement matrix improves the mechanical properties and the durability of HPC [18,19].…”
Section: Introductionmentioning
confidence: 99%